2017
DOI: 10.1155/2017/3149426
|View full text |Cite
|
Sign up to set email alerts
|

The Hyperlipidemia Caused by Overuse of Glucocorticoid after Liver Transplantation and the Immune Adjustment Strategy

Abstract: The overuse of glucocorticoid may cause the metabolic disorders affecting the long term outcome of liver transplantation. This study aims to investigate the immune adjustment strategy by decreasing use of glucocorticoid after liver transplantation. The follow-up study was carried out on liver function and lipid metabolism. This study included adult recipients of liver transplantation. There were 3 groups according to their use of glucocorticoid: long term (>3 months, n = 18), short term (<3 months, n = 20), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
1
4
0
1
Order By: Relevance
“…Cr (III) would be beneficial for treating dyslipidemia present in RA that gives rise to premature atherosclerosis in the disease (Arias de la Rosa et al 2018), as what happened when Cr (III) was tested for prevention of atherosclerosis in diabetes (Qi et al 2020 ). In the current study Cr (III) also showed a low atherogenic index and was significantly lower than prednisolone index which gives another advantage for Cr (III) in comparison with prednisolone which is known to cause dyslipidemia (Meng et al 2017 ).…”
Section: Discussionsupporting
confidence: 49%
“…Cr (III) would be beneficial for treating dyslipidemia present in RA that gives rise to premature atherosclerosis in the disease (Arias de la Rosa et al 2018), as what happened when Cr (III) was tested for prevention of atherosclerosis in diabetes (Qi et al 2020 ). In the current study Cr (III) also showed a low atherogenic index and was significantly lower than prednisolone index which gives another advantage for Cr (III) in comparison with prednisolone which is known to cause dyslipidemia (Meng et al 2017 ).…”
Section: Discussionsupporting
confidence: 49%
“…Another important limitation is the potential worsening of dyslipidemia. Glucocorticoids have been shown to increase triglyceride levels and decrease high-density lipoprotein cholesterol levels ( 53 ). Therefore, the therapeutic use of glucocorticoids should be carefully considered individually considering the potential risks and benefits of targeted delivery.…”
Section: Discussionmentioning
confidence: 99%
“…As long-term use of corticosteroids is associated with complications such as diabetes, hypertension, myopathy, osteoporosis, and increased risk of infection, 59,60 safe and effective treatment options that enable corticosteroid taper are desirable. All patients who received itacitinib in the present study discontinued or reduced corticosteroid use by day 56.…”
Section: Discussionmentioning
confidence: 99%